PENGUATAN PERAN SEKOLAH DAN ORANG TUA DALAM MEMBANGUN KESEIMBANGAN AKADEMIK DAN NON AKADEMIK PESERTA DIDIK - Faza, Najmi; Arifiana, Nuril Ameilia (Universitas Al-Amien Prenduan, 2024)
The balance between academic achievement and non-academic activities is an important factor in shaping students who are well-rounded, creative, and competitive. However, in practice, many schools and parents still focus solely on academic achievement without considering the importance of developing non-academic potential. This community service program aims to strengthen the collaborative role between schools and parents in optimizing student potential through an approach that balances academic and non-academic pursuits. The program is implemented through training, mentoring, and workshops involving teachers, school committees, and parents. These activities focused on increasing understanding of the concept of holistic education, managing study time and extracurricular activities, and effective communication strategies between schools and families. The results of the community service show an increase in awareness and synergy between schools and parents in supporting the balanced growth and development of students. Teachers have become more open to the importance of non-academic activities as a means of character building, while parents better understand that academic achievement is not the only indicator of a child's success. The collaboration that has been built has resulted in a more supportive and adaptive educational environment for the overall developmental needs of students.